Plasmodium ovale malaria in Brazil: report of an imported case with a prolonged incubation period - Limongi, Jean Ezequiel; Costa, Daniela Camargos; Carvalho, Luzia Helena; Lopes, Iris Sousa; Silva, Alcides Assis; Ferreira, Marcelo Simão (The Journal of Infection in Developing Countries, 2014)
We report the first case of imported Plasmodium ovale in Brazil, confirmed using both conventional microscopy and PCR-based protocols. The patient was a 36-year-old Brazilian male who had been working as a miner in Cabinda Province, Angola. Based on his travel history, the parasite was dormant for at least two years. The relatively long period of incubation of P. ovale may obscure the link between exposure and disease. The recent increase in the number of people travelling to regions where P. ovale is endemic, suggests that a PCR-based protocol should be included as a complementary tool for malaria reference laboratories.